Regulatory challenges for 3D printed personalized medical devices (Transactions on Additive Manufacturing Meets Medicine, 2020)
3D printing can be used to manufacture both standard devices, as well as personalized devices. For the latter, a number of jurisdictions around the world allow those products to enter the market not following a normal conformity assessment. As an example, the EU has the system of custom-made devices. As regulators realize that 3D printing leads to a strong growth in personalized devices, these regimes have become more restrictive. This presentation aims to provide a brief overview for some jurisdictions, including the EU, USA and Australia.
Keywords: personalized medical devices